PRINSIP DASAR PEMBANGUNAN DAN PERTUMBUHAN EKONOMI ISLAM - Lalu Iswandi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
Along with the times, human life aspects of doing business to meet the needs and better circumstances of life for the sake of staring at a bright future increasingly diverse. Therefore, Islam offers a development system and fosters community economic for the creation of the society-welfare. The concept offered by the Islamic in the development and economic growth is not only applicable to Muslims but also applicable universally. That is the meaning of Islam as a mercy to all the worlds (rahmatanlilalamin).In this case there are several points to be used as a rationale to look at the concept and development activity as well as the Islamic economic growth. First , the basic principles of Islamic economic development. Second, the basic principle of Islamic economic growth. Third, the measure of Islamic economic growth. And the Fourth , the difference between development and economic growth . In the life and the formation of qualified human character, Islam basing economic development on the formation of each individual that is geared towards divinity as control every human action in daily mu'amalah. people who prioritize economic changes only with regard to spiritual, they still do deviations from the law of Allah, each economic actors and the government plays an important role for the creation of well-being in every layer of society.